2022
DOI: 10.1088/1572-9494/ac85d9
|View full text |Cite
|
Sign up to set email alerts
|

Rayleigh–Taylor instability under multi-mode perturbation: Discrete Boltzmann modeling with tracers

Abstract: The two-dimensional Rayleigh-Taylor Instability (RTI) under multi-mode perturbation in compressible flow is probed via the Discrete Boltzmann Modeling (DBM) with tracers. The distribution of tracers provides clear boundaries between light and heavy fluids in the position space. Besides, the position-velocity phase space offers a new perspective for understanding the flow behavior of RTI with intuitive geometrical correspondence. The effects of viscosity, acceleration, compressibility, and Atwood number on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…From the perspective of physical modeling, the DBM is approximately equivalent to a continuous fluid model plus a coarse-grained model describing TNE effects. In recent years, the DBM has been widely used in the numerical study of the RT instability in compressible fluids and has made remarkable progress [31][32][33][34][35][36][37][38][39][40]. For example, Lai et al, studied the impact of compressibility on the RT instability by using the DBM and found that the compressibility effect and the global TNE intensity exhibit opposite tendencies in the early and later stages of the RT instability [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the perspective of physical modeling, the DBM is approximately equivalent to a continuous fluid model plus a coarse-grained model describing TNE effects. In recent years, the DBM has been widely used in the numerical study of the RT instability in compressible fluids and has made remarkable progress [31][32][33][34][35][36][37][38][39][40]. For example, Lai et al, studied the impact of compressibility on the RT instability by using the DBM and found that the compressibility effect and the global TNE intensity exhibit opposite tendencies in the early and later stages of the RT instability [31].…”
Section: Introductionmentioning
confidence: 99%
“…Ye et al, studied the effect of Knudsen number on the RT instability in 2-D compressible fluid using the DBM [37]. Li et al, simulated the nonlinear evolution of the multi-mode compressible RT instability using the DBM [38]. Chen et al, studied the impacts of viscosity, heat conduction, and Prandtl number on 2-D RT instability by using the multi-relaxation time DBM simulation with gravity [39].…”
Section: Introductionmentioning
confidence: 99%
“…Discrete Boltzmann method (DBM) is a modeling and analysis method based on kinetic theory in statistical physics [73][74][75][76][77][78][79][80] . It provides various measures to detect, describe and exhibit the complex Thermodynamic Non-Equilibrium (TNE) behaviors, and has brought a series of new insights in several fields in recent years, such as multiphase flow [81][82][83][84][85] , rarefied gas flow 86,87 , combustion and detonation [88][89][90][91][92][93][94][95][96][97] , hydrodynamic instabilities [98][99][100][101][102][103][104][105] , etc. In contrast to conventional CFD methods, DBM is not restricted by the continuous and nearequilibrium assumptions, and can describe the cases of high Knudsen (Kn) number which contain strong TNE and noncontinuity effects.…”
Section: Introductionmentioning
confidence: 99%